Do children in India grow well into adolescents? Longitudinal analysis of growth transitions from Young Lives panel survey in India. (January 2022) - Das, S.K.; Burma, A.D.; Amudhan, S.; Mishra, V.; Mahapatra, P.; Ashok, A.; Philip, M.
Abstract: Objectives: Studies that examined the growth during late childhood and early adolescence beyond 8 years of age are very limited. Further, most studies have used dichotomized classification of stunting, thereby limiting the understanding of moderate stunting in childhood growth trajectory. We aimed to examine the course of stunting from childhood to adolescence by undertaking robust analyses of the Young Lives Survey (YLS) longitudinal data from India using multilevel categorization of stunting. Study design: Retrospective cohort analysis was undertaken from YLS in India among 1827 children from the younger cohort born in 2001–02 with complete follow-up data in all five rounds of YLS collected in 2002, 2006, 2009, 2013, and 2016. Methods: A three-state multistate Markov model (not stunted, moderate, severe) was performed to estimate annual transition probabilities, mean sojourn-time, and transition-specific risk factors. Results: Between Round-one and Round-five, cross-sectional prevalence of severe stunting decreased from 10.4% (95% confidence interval [CI]: 7.8%, 13.7%) to 5.3% (95% CI: 3.8%, 7.3%), while moderate stunting increased from 19.9% (95% CI: 16.3%, 23.9%) to 21.7% (95% CI: 18.4%, 24.9%). Mean Sojourn time estimation indicated a relatively concise state for moderate stunting. The stunting trajectory had shown gender differential where more faltering to severe stunting and lower recovery to the normal state was observed among girls between 8 and 12 years and among boys between 12 and 15 years. Compared with boys, girls had 40% excess likelihood (Hazard Ratio: 1.40; 95% CI 1.00 to 1.95) for moderate-to-severe stunting transition and also had 19% excess likelihood (Hazard Ratio: 1.19; 95% CI 1.01 to 1.40) of favorable transition (moderate-to-non-stunted). Conclusions: The transition trajectory highlights preadolescence, especially among girls, as an additional window of opportunity to ensure better nutrition in adolescent life. With a fifth of adolescents living in India, study findings call for coordinated, multisectoral, age-appropriate, and gender-responsive approach to take India closer to meeting SDG-2.